2014 IEEE International Symposium on Information Theory 2014
DOI: 10.1109/isit.2014.6875241
|View full text |Cite
|
Sign up to set email alerts
|

The impact of phase fading on the dirty paper coding channel

Abstract: The impact of phase fading on the classical Costa's dirty paper coding channel is studied. We consider a variation of this channel model in which the amplitude of the interference sequence is known at the transmitter while its phase is known at the receiver. Although the capacity of this channel has already been established, it is expressed using an auxiliary random variable and as the solution of a maximization problem. To circumvent the difficulty evaluating capacity, we derive alternative inner and outer bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 11 publications
(22 reference statements)
1
22
0
Order By: Relevance
“…VI. The conditions in (7) indeed reflect the interpretation in Fig. 4: this term is the smallest distance between two contiguous regions in X + cAS when X is restricted to be an integer number in ⌈ √ P ⌉ .…”
Section: Wffd-ncsi Channelsupporting
confidence: 64%
See 2 more Smart Citations
“…VI. The conditions in (7) indeed reflect the interpretation in Fig. 4: this term is the smallest distance between two contiguous regions in X + cAS when X is restricted to be an integer number in ⌈ √ P ⌉ .…”
Section: Wffd-ncsi Channelsupporting
confidence: 64%
“…Here in is shown that the rate loss from full state pre-cancellation is vanishing, since state and input still combine in a predictable manner. In [7], we derived the approximate capacity for the WDP channel in which the state is multiplied by uniform binomial fading by further develop bounding techniques originally developed in [8]. The results in [7] are further extended in [9] to include more general fading distribution, although restricted to the case of discrete support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [7], the first inner and outer bounds to capacity are obtained while [8] studies the outage probability for this model. In [9], we show the approximate capacity of this model for some classes of the phase fading. Achievable rates under Gaussian signaling are derived in [10] for the case of Gaussian distributed fast fading.…”
Section: Introductionmentioning
confidence: 99%
“…In [14] algorithms are also proposed to determine the optimal linear pre-coding strategies which are shown to outperform Costa's linear assignment in the multiple antenna setting. In [15], we derive the capacity to within a constant gap for the channel in which the fading only takes two possible values: this result is extended in [16] to include more general fading distribution and to consider the case in which the fading sequence is not known either at the transmitter or at the receiver.…”
Section: Introductionmentioning
confidence: 99%